Transactional sex and HIV infection among commercial farm workers in South Africa - Idris Durojaiye; Nkechi Obisie-Nmehielle; Latifat Ibisomi (AOSIS, 2020)
Background: High prevalence of HIV infection has been reported among commercial farm workers in South Africa, but studies of the role of transactional sex in this epidemic is limited. Objective: This study seeks to examine the association between transactional sex and HIV infection among commercial farm workers in South Africa. Methods: This is a cross-sectional secondary data analysis of the Integrated Biological and Behavioural Surveillance Survey by the International Organization of Migration among farm workers in Mpumalanga and Limpopo Provinces, South Africa in 2010. The study included 2,758 sexually active farm workers. The outcome variable was HIV infection while the main explanatory variable was engagement in transactional sex. Other explanatory variables were sex, age, marital status, number of sex partners, food security, recent history of sexually transmitted infection, condom use at last sex with non-regular partner, history of sexual violence and migration status. Bivariate and multivariable logistic regression analyses were done to obtain unadjusted and adjusted odds ratios of the association between transactional sex and HIV infection. Results: Engagement in transactional sex was common (19%) but not significantly associated with HIV infection (OR 1.1; CI 0.57-2.44). Female sex (1.93; 1.60-2.32), age 25 to 44 years, recent STI (OR 1.37; CI 1.18-1.58) and sexual violence (OR 1.39; CI 1.19-1.63) were significant risk factors for HIV infection. Conclusion: Risky sexual behaviours were common among the farmworker population. HIV prevention interventions should include behavioural change communication and improved access to healthcare for STI and HIV treatment.